2017
DOI: 10.1111/echo.13744
|View full text |Cite
|
Sign up to set email alerts
|

Pulmonary arterial pressure detects functional mitral stenosis after annuloplasty for primary mitral regurgitation: An exercise stress echocardiographic study

Abstract: The RMA for degenerative MR was associated with a functional stenosis and the PAP at rest and at peak exercise discriminated low exercise capacity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…Exercise stress tests can diagnose patients with subclinical functional MS after mitral valve repair by determining the effective orifice area index and pulmonary arterial pressure that are associated with exercise capacity. 13,14) Otherwise, assessments of follow-up echocardiographic data may be required to prove the association among the aortomitral angle, TMPG, LA size, and AA events. In addition, several other explanations for the negative effect of a small aorto-mitral angle have been reported in previous studies.…”
Section: Discussionmentioning
confidence: 99%
“…Exercise stress tests can diagnose patients with subclinical functional MS after mitral valve repair by determining the effective orifice area index and pulmonary arterial pressure that are associated with exercise capacity. 13,14) Otherwise, assessments of follow-up echocardiographic data may be required to prove the association among the aortomitral angle, TMPG, LA size, and AA events. In addition, several other explanations for the negative effect of a small aorto-mitral angle have been reported in previous studies.…”
Section: Discussionmentioning
confidence: 99%
“…Although using a complete ring has 2 of 16 been associated with a lower MR recurrence rate than a partial band or no annuloplasty at all [11][12][13], it also results in a higher incidence of functional mitral stenosis (FMS) [14,15]. FMS, primarily caused by restrictive annuloplasty, is associated with inferior exercise tolerance, failed left atrial remodeling, new-onset atrial fibrillation (Af), elevated pulmonary artery pressure, residual tricuspid regurgitation (TR), and poor long-term prognosis [16][17][18][19][20].…”
Section: Introductionmentioning
confidence: 99%
“…FMS is defined as a resting mean trans-mitral pressure gradient (TMPG) of >5 mmHg or MV area of <1.5 cm 2 at rest [20,21], and a mean TMPG of >15 mmHg and pulmonary artery systolic pressure of >60 mmHg during exercise [22]. Previous studies [23,24] have indicated that the use of rigid or undersized rings may increase the risk of a smaller subsequent MV area, leading to FMS.…”
Section: Introductionmentioning
confidence: 99%